PERSPECTIVES OF SERBIAN-ALBANIAN RELATIONS IN THE LIGHT OF THE „OPEN BALKANS“ INITIATIVE - Stanković, Marko; Krstić, Zoran (National interest, 2023)
The historical legacy of Serbian-Albanian relations, as well as the process of liberation and the establishment of modern states, can represent a burden that, due to its specific nature, often results in the adoption of prejudices that create public opinion in support of policies contrary to the general interests of citizens who live today in the area where Serbian-Albanian political positions intersect. The presence of the consequences of the Serbian-Albanian conflicts at the end of the 20th and the beginning of the 21st century slows down the establishment of healthy political relations that should benefit not only Serbia and Albania, but also the entire Western Balkan region. In the era when Serbia, North Macedonia and Albania are trying to become part of the European Union, there are numerous obstacles and a lack of support from European countries on this path, so these countries have decided on regional political and economic integration. The development of regional integration and the necessity of cooperation of states in the regional political context was further developed by Ernst Hass, noting that in overall international political relations integration actually becomes necessary and represents the correctness of the international action of states (Hass, 2008). Accordingly, these countries decided to establish better political and economic relations, and improve them through the "Open Balkans" initiative, for which they again paradoxically expect help that was absent in the original processes of European integration. Such a bold step represents a mini-precedent in the European history of integration, bearing in mind that these countries have created a new mechanism of progress in the direction of adopting European values ​​and establishing European standards. Although burdened, impossible, difficult and unsuccessful in appearance, Serbian-Albanian relations have a future through such initiatives. This paper will try to answer the question: Is Serbian-Albanian cooperation possible?; What are the development paths of Serbian-Albanian relations?. The issues of defining the culprit for past conflicts will not be considered in this paper, nor will the paper focus on the consequences of past conflicts, because that would be a road without a destination in which precious time passes and the Serbian-Albanian political space recedes.